Perspectives of healthcare workers on chemotherapy treatment in selected facilities in Kenya - Mchidi, Nebert; Oyore, John; Ogweno, Gordon (International Journal Of Community Medicine And Public Health, 2024)
Healthcare workers are better placed to recognize the drivers of the cancer health care experience by patients, an important ingredient in shaping the realization of the third pillar of the Kenya National Cancer Control Strategy. To adequately assess health systems and identify bottlenecks in cancer care, a triumvirate of factors including patient, health system, and health workforce need to be considered. For context, Kenya’s health ministry reports that 70-80% of cancer patients in Kenya are diagnosed at an advanced stage of the disease, a pointer to a gap in the detection and linkage of cancer patients to care. With increasing cancer incidence, cancer treatment centres will experience increased patient loads and will be overwhelmed in addressing individualized patient needs. Health workers can offer information on what the cancer care situation is currently like, and lessons drawn from their experience used to create adequate health systems. An adequate health system has been fashioned as one that not only address patients’ needs but also generates adequate information needed to inform the transformation of those systems in line with the goals contemplated in quality healthcare. The aim of this study was to explore (i) the perspectives of health workers on the characteristics of cancer patients seen in treatment facilities and (ii) the capacity of cancer treatment facilities in the management of cancer. A key informant approach using semi-structured interviews was carried out with sampled respondents consisting of health workers (n=12) in selected facilities who were providing outpatient chemotherapy treatment. Data analysis involved transcribing the interviews into first-person narratives and then analysed using the three-dimensional framework. Subsequently, thematic analysis was applied to generate themes. Data analysis generated three main themes: characteristics of patients receiving chemotherapy treatment, capacity of the facility to manage cancer patients, and factors that hinder effective cancer care provision. Cancer care in Kenya is impeded by poverty, staff shortages, and lack of adequate cancer care. There is a need to reorient cancer care with an emphasis on integrated cancer care delivery modalities.